The Relationship Of Pregnant Women's Knowledge And The Incident Of Hyperemesis Gravidarum In The Atikah Sipolu-Polu Midwifery Clinic - Deli, Fitriana (Benih : Journal of Midwifery, 2023)
Hyperemesis Gravidarum is one of the complications that often occurs in pregnancy. Hyperemesis Gravidarum in 2016 is 1.5-3% of all pregnant women. Most of the causes of maternal death are bleeding, 70-80% of pregnant women experience morning sickness and as many as (25.2%), infection (11.1%), sepsis (15%), hypertension in pregnancy (12%) and also other causes. (8%), for example anemia, malaria, heart disease, diabetes and hyperemesis gravidarum in 2016. The aim of this research is to analyze the relationship between knowledge of pregnant women and the incidence of hyperemesis gravidarum. This type of research is an analytical survey with a cross sectional approach. The sampling technique used Accidental Sampling, namely a sampling technique based on chance and 37 people were sampled. The tool used was a questionnaire with 20 statements. The variables used in this research are independent and dependent variables. The independent variables in this research are knowledge, age, occupation, parity, source of information and the dependent variable in this research is hyperemesis gravidarum. Data processing was done by editing, coding, tabulating, then tested using the Chi-Squer test. The data analysis used was univariate analysis of knowledge of pregnant women with the majority of hyperemesis gravidarum incidents being in the good category as many as respondents (18). The results of the Chi-Squer test showed a p-value of 0.020 <0.20 so that Ho was rejected and Ha was accepted. This research shows the relationship between knowledge of pregnant women and the incidence of hyperemesis gravidarum at the Atikah midwife clinic, Panyabungan District, Mandailing Natal Regency.